Atividades antibacteriana, antifúngica e antioxidante do extrato e das frações proteícas da microalga Synechococcus nidulans cultivada em fotobiorreator - Freire, Elionai Gomes (2021)
Microalgae biomass is useful in several biotechnological applications such as: wastewater treatment, bioremediation of harmful compounds, biofuel, animal and human food, production of cosmetics and medicines. Given its versatility, the objective of this work is to evaluate the antibacterial, antifungal and antioxidant activities of the extract and protein fractions of the microalgal biomass of Synechococcus nidulans. A pre-inoculum of Synechococcus nidulans was inoculated in a rectangular planar plate photobioreactor containing 4 L of NPK culture medium (20:10:20 m / m / m mandatory) under controlled conditions (temperature 25 + 2 °C, photoperiod of 12 h, luminous intensity of 50,000 Lux, sterile aeration and Ph 7.0). After 30 days of cultivation, an average dry biomass yield of 7.12 + 1.3 g.L-1 was obtained. Biochemical analysis of microalgal biomass of S. nidulans presenting 45% proteins, 23% carbohydrates and 12% lipids. The culture was collected and centrifuged at 10,000 x g for 30 min at 25 oC. and the resulting biomass was washed with distilled water through four alternating steps of resuspension and centrifugation to form the total Crude Extract (EBt). To prepare the High Protein Fractions (FRP), 10 mL volumes of EBt were topped up to protein using different saturation levels (0-20%, 20-40%, 40-60% and 60-80%) with sulphate. ammonium Antioxidant activity was determined by measuring the DPPH radical scavenging capacity (2,2-diphenyl-1-picryl-hydrazyl). This assay was performed in microtiter plates (96-well), 10 µL of each tested sample were added to the wells ((EBt, FRP0-20%, FRP20-40%, FRP40-60% and FRP60-80%), in the concentrations of 100 to 1,000 g.mL-1 and 190 µL of the methanolic solution of DPPH (Sigma) at 78 µM. The FRPs showed a DPPH radical scavenging capacity close to 3.0% at low concentrations (100 µg.mL -1) and 7.0% at high concentrations (1000 µg.mL-1) , were well suited to the EBt capacity which was 16.9% and 68.0% at low and high concentrations, respectively. Antifungal was performed by the disk diffusion method, using the fungi: Colletotrichum musae, Candida albicans, Candida kefyr, Aspergillus niger and Aspergillus fumigatus. 1 mg of each sample (EBt, FRP0-20%, FRP20-40%, FRP40 -60% and FRP60-80%) lyophilized was solubilized in PBS buffer pH 7.4 and sterilized in a Millipore filter (0.22 µm).The EBt and FRP 40-60% were the most effective in combating fungi, presenting the bigger inhibition halos. The antibacterial activity on S. epidermidis and S. aureus bacteria was performed according to the broth microdilution assay, in 96-well polystyrene plates. The plate wells were initially filled with 200 µL of each sample (EBt, FRP0-20%, FRP20-40%, FRP40-60% and FRP60-80%) and 100 µL of the suspension of each bacteria tested at a concentration of 2x106 CFU .mL-1. The Minimum Inhibitory Concentration (MIC) was measured through the turbidity of the wells with the aid of a microplate reader (SpectraMax i3) at a wavelength of 620 nm. To determine the Minimum Bactericidal Concentration (MBC), 24 h after incubation, 10 μL of the solution contained in the wells that did not show microbial growth were removed, followed by inoculation in Petri dishes with TSA medium. EBt and FRP 40- 60% showed similar bactericidal capacity for bacteria of the Staphylococcus genus. However, for inhibitory and bactericidal capacity, only EBt proved to be efficient. Thus, the total crude extract from the biomass of Synechococcus nidulans showed excellent antioxidant, antifungal and antibacterial results. As for the protein-rich fractions, only FRP 40-60% showed the best antifungal and antibacterial results.